KM55 in the evaluation of IgA containing glomerular diseases - Rahul Raj (Karger Publishers, 2021)
Introduction: Mucosal derived galactose deficient IgA is central to the pathogenesis of primary IgA nephropathy. Recent reports suggest similar pathogenesis in Henoch Schonlein purpura and secondary IgA nephropathy. Its role in other IgA containing glomerular diseases is still under investigation. It can be detected in glomeruli with the recently described antibody, KM55. We aimed to evaluate the role of KM55 by immunostaining a wide spectrum of IgA containing glomerular diseases. Methods: After standardization and co localization in a case of IgA nephropathy, a spectrum of 60 cases including IgA nephropathy, Henoch Schonlein purpura, chronic liver disease related IgA nephropathy, other secondary IgA Nephropathy, IgA dominant/co dominant membranoproliferative glomerulonephritis and lupus nephritis were subjected to immunofluorescence with KM55. KM55 was used to resolve diagnostic dilemma in cases of IgA deposition with confounding histology. Results: The group of primary IgA Nephropathy (17 cases), Henoch Schonlein purpura (4 cases) and secondary IgA nephropathy (19 cases) including chronic liver disease showed 2 -3+ granular staining with KM55 suggesting mucosal derived IgA. In contrast, cases of IgA dominant/co dominant membranoproliferative glomerulonephritis (8 cases) and lupus nephritis (12 cases) were negative for KM55, suggesting systemic derivation of IgA. In cases of IgA deposition with confounding histology such as membranoproliferative or diffuse endocapillary proliferative pattern, KM55 helped to resolve the diagnosis. Discussion/Conclusion: This cross-sectional study concludes that KM55 is useful in the evaluation of IgA containing glomerular diseases from a pathogenetic perspective, and is a practical tool in resolving differential diagnosis in cases with overlapping histopathologic features.